Structure and factors of the risk of premature birth - Аizada Marat; Talshyn Ukybassova (National Scientific Medical Center, 2017)
Objective. To study the structure and risk factors of premature birth. Methods. Prospective open-label non-randomized clinical trial. The study included 11 861 births, including 1806 - premature (15.2%) in the CF "UMS of the National Research Center for Maternity and Childhood." The odds ratio (OR), the confdence interval (CI) of risk factors for the development of preterm birth have been calculated. Results. When studying the social portrait of prematurely giving birth to women: the level of education (OR - 2.7, SE - 0.29, CI (95%) 1.5-4.8;) employment (OR-2.4, SE-0, 29; CI (95%) 1.3-4.1;) and the woman's place of residence (OR 1.5, SE 0.29, CI 95% 0.9-2.7) are statistically signifcant risk factors for premature birth. The study of obstetrical anamnesis of pregnant women revealed the following: 14.2% - primitive, 85.8% - repeat pregnancy, 26.3% - with a syndrome of previous perinatal losses (2 or more spontaneous abortions), 32.2% - previous premature births, 2, 4% - with cervical insufciency. Conclusion. The main risk factors for premature birth are cervical insuffciency, repeated pregnancies with a parity of more than 4 (OS-1.19, SE-0.3, CI (95%) 0.7-2.2;), the presence of premature birth and fetal loss in the history (OR-2.66, SE-0.35, CI (95%), 1.3-5.3;), birth of small children (OR-2.38; SE-0.37; CI (95%) 1.2-5.1;). The social portrait of women with preterm birth appears as follows: age 20 to 34 years, predominantly in rural areas, housewives with low and medium education, with habitual loss of pregnancy or previous premature birth, cervical insufciency. Family planning, pre-birth training for a prospective mother and conducting preventive measures in pregnant high-risk groups for premature birth can be a condition for reducing the frequency of preterm labor